Baseline adjustment methodology in a shared water savings contract under serious drought conditions - Jacobs, H.E.; Du Plessis, J.L.; Nel, Nicole; Gugushe, S.; Levin, S. (Water S. A., 2020)
Baselines are often employed in shared water saving contracts for estimating water savings after some type of intervention by the water service company. An adjustment to the baseline may become necessary under certain conditions. Earlier work has described a number of relatively complex methods for baseline determination and adjustment, but application in regions faced with relatively limited data becomes problematic. If the adjustment were determined before finalising the contractual matters, it would be possible to gather the required data in order to determine the adjustment. However, in cases where no adjustment was fixed prior to the contract, a method is required to determine an adjustment mid-contract based on whatever data are available at the time. This paper presents a methodology for baseline adjustment in an existing shared water savings contract and explains how adjustment could be determined mid-contract, under conditions of limited data. The adjustment compensates for expected reduced water consumption due to external influences induced by serious water restrictions, typically introduced during periods of drought. The fundamental principle underpinning the baseline adjustment methodology presented in this paper involved segregating real water losses from the actual consumption of end-users, preferably by analysing the minimum night flow. In the absence of recorded night flows, an alternative procedure involving the minimum monthly consumption pre- and post-baseline was employed. The baseline adjustment method was subsequently applied in a South African case study, reported on separately. This technique is helpful because adjustments could be determined without adding unnecessary complexity or cost, and provides a means to resolve disputes in cases where unexpected savings occur mid-contract.